Attitudes of Students with Disabilities in the Jordanian University Community in the Central Region towards Distance Learning and the Level of their Interactions with it During the Covid-19 Pandemic - Abd Alfattah Almakanin, Hisham; M. Alodat, Ali; Abdullah AlAdwan, Duaa; Mohammad Al-Hiary, Ghaleb (Dirasat: Human and Social Sciences, 2022)
This study aims to identify the attitudes of students with disabilities in the Jordanian universities community in the center towards distance learning and the level of their interactions with it during the Corona Covid-19 pandemic. The study participants were (205) students with disabilities, who responded to the study scale that was developed specially to this study and consists of (62) items divided into two main dimensions: Attitudes, which consisted of (39) items and Interaction, which consisted of (23) items, and the researchers verified the validity and reliability indicators of the scale. The results indicated that the attitudes of students with disabilities in the Jordanian university community towards distance learning were negative and revealed that there were differences in the attitudes of students with disabilities towards distance learning due to the type of their disabilities and knowledge of using technological communication tools. On the other hand, the results found no differences attributable to the student’s gender or the type of learning platform. The results also showed a moderate level of interactions among students with disabilities with distance learning, in addition to the lack of a correlation between the attitudes of students with disabilities towards distance learning and their level of interactions with distance learning.